2022
DOI: 10.3748/wjg.v28.i32.4716
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of different types of solid focal liver lesions using two-dimensional shear wave elastography

Abstract: BACKGROUND The clinical management and prognosis differ between benign and malignant solid focal liver lesions (FLLs), as well as among different pathological types of malignant FLLs. Accurate diagnosis of the possible types of solid FLLs is important. Our previous study confirmed the value of shear wave elastography (SWE) using maximal elasticity (Emax) as the parameter in the differential diagnosis between benign and malignant FLLs. However, the value of SWE in the differential diagnosis among d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our previous studies have shown that the value of SWE with Emax in the differential diagnosis between benign and malignant focal liver lesions or among different pathological types of malignant focal liver lesions[ 15 ]. In this study, we found that the Emax of HCCs and the Emax of the periphery of HCCs were significantly different between MVI-positive HCCs and MVI-negative HCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that the value of SWE with Emax in the differential diagnosis between benign and malignant focal liver lesions or among different pathological types of malignant focal liver lesions[ 15 ]. In this study, we found that the Emax of HCCs and the Emax of the periphery of HCCs were significantly different between MVI-positive HCCs and MVI-negative HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound elastography, especially quantitative shear wave elastography (SWE), plays an important role in hepatic imaging[ 15 - 17 ]. Compared with CEUS, contrast-enhanced computed tomography, or contrast-enhanced MRI, SWE has the advantage of the absence of contrast agent allergy and is generally less expensive and less time-consuming than other methods, making it a more practical option for many medical facilities.…”
Section: Introductionmentioning
confidence: 99%